Pengaruh Kualitas Sarana Belajar Terhadap Motivasi Belajar Mahasiswa Di Kampus II UIN Sumatera Utara Medan - Farhana; Abdul Fattah Nasution; Ayu Putri Julia; Ryan Fazli Zulna; Marhatul fatwa (Insan Zenius Ilmiah, 2024)
This research aims to examine the influence of the quality of learning facilities on student learning motivation. The learning facilities in question include classrooms, libraries, laboratories, technology access, discussion rooms, as well as health and security support facilities. The methodology used in this research is a quantitative survey using questionnaires distributed to students at various universities. The research results show that the quality of learning facilities has a significant influence on student learning motivation. Comfortable and complete facilities, such as clean and air-conditioned classrooms, resource-rich libraries, laboratories equipped with modern equipment, and good access to technology, increase students' learning motivation. Apart from that, good campus health and security support facilities also contribute to increasing learning motivation. In conclusion, educational institutions need to improve the quality of learning facilities to create a conducive environment for the learning process and increase student learning motivation.